Microplastics in the digestive tract of Gryllus pennsylvanicus crickets in a biosolid – treated agricultural field - Emily R. McColville; Marshall W. Ritchie; Jesse Vermaire; David Lapen; Heath A. MacMillan; Jennifer F. Provencher; Jane E. Allison (Scientific Reports)
Abstract Microplastic ubiquity, its general toxicology, and its suitability for ingestion by biota are leading ecological and human health concerns. Microplastics are abundant in terrestrial environments including agricultural settings where municipal biosolids applied as fertilizers show high levels of microplastics. Microplastic ingestion by omnivorous insects in the environment is not well explored. To determine whether crickets eat microplastics in the wild, we examined the digestive tracts of 50 crickets collected from a research site in Ontario, Canada. Crickets were caught in three locations: a crop field amended with dewatered municipal biosolids, along the untreated edge of the field, and along a nearby tree line. Over half of the dissected crickets contained microplastics. A total of 87 microplastics (31–2548 μm) were found (60 microfragments; 27 microfibers). Using FTIR, we determined 66% of the microfragments were plastic polymers although match quality was low, likely due to exposure to multiple degradation processes (e.g. laundry, wastewater processing, ingestion by animals). Trap location did not influence the number of crickets ingesting microplastics. We present evidence that lab-reared crickets of the same species break down ingested microplastics into smaller fragments using manufactured polyethylene spheres, and discuss the possibility that generalist ground dwelling insects like crickets contribute to the active transport and biotransformation of microplastics, with potential cascading effects on microplastic movement through the food webs.